2023
DOI: 10.1609/icwsm.v17i1.22158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feedback on Drug Consumption Disclosures on Social Media

Abstract: Deaths due to drug overdose in the US have doubled in the last decade. Drug-related content on social media has also exploded in the same time frame. The pseudo-anonymous nature of social media platforms enables users to discourse about taboo and sometimes illegal topics like drug consumption. User-generated content (UGC) about drugs on social media can be used as an online proxy to detect offline drug consumption. UGC also gets exposed to the praise and criticism of the community. Law of effect proposes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Past research has suggested that Reddit is a popular social media platform well suited for substance-related research due to its large number of users with diverse backgrounds, which facilitates longitudinal data analysis and insights into the evolving nature of substance use and discussions [ 30 ]. Various studies have indicated that engaging in substance-related discussions can be a strong marker of an individual’s experience with substance use [ 26 , 28 , 31 ]. For our data set, we focus on Reddit, a prevalent social media platform where individuals can anonymously participate in topic-centered communities known as “subreddits.” Each subreddit operates under its own set of rules to moderate posts and comments, offering unfiltered discussions with less interference from overarching platform policies, distinguishing Reddit as an ideal platform for analysis of substance-related conversations [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has suggested that Reddit is a popular social media platform well suited for substance-related research due to its large number of users with diverse backgrounds, which facilitates longitudinal data analysis and insights into the evolving nature of substance use and discussions [ 30 ]. Various studies have indicated that engaging in substance-related discussions can be a strong marker of an individual’s experience with substance use [ 26 , 28 , 31 ]. For our data set, we focus on Reddit, a prevalent social media platform where individuals can anonymously participate in topic-centered communities known as “subreddits.” Each subreddit operates under its own set of rules to moderate posts and comments, offering unfiltered discussions with less interference from overarching platform policies, distinguishing Reddit as an ideal platform for analysis of substance-related conversations [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, we used the strategy of breaking ties by selecting the highest risk level as the majority label. The rationale behind this tie-breaking approach lies in the assumption that when Reddit users begin engaging in discussions within higher risk level subreddits, they likely already possess some level of experience or familiarity with those particular drugs [ 26 , 28 , 31 ]. By assigning the higher risk level as the majority label in cases of ties, we aimed to capture the progression or transition of Reddit users toward subreddits associated with potentially greater risk.…”
Section: Methodsmentioning
confidence: 99%